Strategy for Developing Tourism Based on Local Communities, 2023–2024 - Wa Ode Vivin; yusti yusti; Faturacman Alputra Sudirman; Saidin Saidin (PROVIDER JURNAL ILMU PEMERINTAHAN, 2026)
Technological advancements and global changes have significantly influenced tourism development, especially in promoting inclusive and sustainable models such as Community-Based Tourism (CBT). This study aims to conduct a systematic literature review on the strategies for developing community-based tourism in Indonesia during the 2023–2024 period. The review seeks to identify dominant themes, trends, and strategic approaches used to empower local communities in tourism management and development.Data were collected using the Publish or Perish application with Google Scholar as the primary source. A total of 321 relevant articles were selected based on specific keywords. Bibliometric analysis was conducted using VOSViewer (version 1.6.20) to visualize keyword networks and research clusters, while thematic qualitative analysis was applied to interpret emerging strategies.development, with research grouped into three main clusters: (1) strategies focusing on cultural and environmental preservation through community engagement, (2) CBT models that emphasize participation, empowerment, and local capacity building, and (3) strategies integrating local potential, digital innovation, and multi-stakeholder collaboration. The study also highlights the crucial role of digital platforms and social media in promoting tourism narratives and engaging wider audiences.This research emphasizes that successful community-based tourism requires strong local involvement, institutional support, and adaptive digital strategies. The findings offer theoretical insights and practical guidance for policymakers, tourism stakeholders, and local communities in strengthening tourism governance and resilience.